Electrodes: Reduced Graphene Oxide Electrodes with Wrinkled Surface for Nonvolatile Polymer Memory Device Compatibility (Small Methods 7/2018). Issue 7 (12th July 2018) - Chen, Jie; Wang, Xiangjing; Lu, Hang; Liu, Zhengdong; Xiu, Fei; Ban, Chaoyi; Zhou, Zhe; Song, Mengya; Ju, Shang; Chang, Qing; Liu, Juqing; Huang, Wei
Abstract : A general strategy for high‐performance nonvolatile polymer memory devices, with wrinkled reduced graphene oxide films as electrodes and common insulating polymers as active layers, is proposed by Juqing Liu, Wei Huang, and co‐workers in article number1800048 . The fabricated device exhibits nonvolatile write‐once–read‐many (WORM)‐type memory, with a low switching voltage, high ON/OFF ratio, long retention time, excellent reproducibility, and flexibility, demonstrating great potential in permanent archival storage applications.